Effect of herbicides on weed dynamics, efficiency and yield of linseed : Effect of herbicides on weed dynamics, efficiency and yield of linseed - S K DWIVEDI; C S PUHUP (Journal of Oilseeds Research, 2020)
The lowest weed density and weed dry matter was observed with hand weeding twice [(21 and 45 days after sowing (DAS)]. Among herbicidal treatments, the lowest value was observed with isoproturon + metsulfuron-methyl (1 kg + 4 g/ha) as post-emergence application. The dry matter accumulation at 30 and 60 DAS was recorded significantly higher under hand weeding twice which was at par with the post-emergence application of isoproturon + metsulfuron-methyl (1 kg + 4 g/ha), metsulfuron-methyl (4 g/ha) post-emergence, isoproturon 1 kg/ha postemergence and pendimethalin (1 kg/ha) pre-emergence followed by post-emergence application of metsulfuronmethyl (4 g/ha).The seed yield was recorded significantly higher under treatment of hand weeding twice (at 21 and 45 DAS) which was statistically comparable to the post-emergence isoproturon + metsulfuron-methyl (1 kg + 4 g/ ha), metsulfuron-methyl (4 g/ha), pendimethalin (1 kg/ha) pre-emergence followed by metsulfuron-methyl (4 g/ha) postemergence and isoproturon (1 kg/ha) post-emergence. Among the herbicides applications, weed control efficiency at 90 DAS and at harvest was recorded maximum with the application of isoproturon + metsulfuron- methyl (1 kg + 4 g/ha) and minimum was noted with the application of imazethapyr (75 g/ha).